Mycobacterium leprae induces a tolerogenic profile in monocyte‐derived dendritic cells via TLR2 induction of IDO. Issue 1 (11th October 2020) - Oliveira, Jéssica A. P.; Gandini, Mariana; Sales, Jorgenilce S.; Fujimori, Sérgio K.; Barbosa, Mayara G. M.; Frutuoso, Valber S.; Moraes, Milton O.; Sarno, Euzenir N.; Pessolani, Maria C. V.; Pinheiro, Roberta O.
Abstract: The enzyme IDO‐1 is involved in the first stage of tryptophan catabolism and has been described in both microbicidal and tolerogenic microenvironments. Previous data from our group have shown that IDO‐1 is differentially regulated in the distinctive clinical forms of leprosy. The present study aims to investigate the mechanisms associated with IDO‐1 expression and activity in human monocyte‐derived dendritic cells (mDCs) after stimulation with irradiated Mycobacterium leprae and its fractions. M. leprae and its fractions induced the expression and activity of IDO‐1 in human mDCs. Among the stimuli studied, irradiated M. leprae and its membrane fraction (MLMA) induced the production of proinflammatory cytokines TNF and IL‐6 whereas irradiated M. leprae and its cytosol fraction (MLSA) induced an increase in IL‐10. We investigated if TLR2 activation was necessary for IDO‐1 induction in mDCs. We observed that in cultures treated with a neutralizing anti‐TLR2 antibody, there was a decrease in IDO‐1 activity and expression induced by M. leprae and MLMA. The same effect was observed when we used a MyD88 inhibitor. Our data demonstrate that coculture of mDCs with autologous lymphocytes induced an increase in regulatory T (Treg) cell frequency in MLSA‐stimulated cultures, showing that M. leprae constituents may play opposite roles that may possibly be related to the dubious effect of IDO‐1 in the different clinical forms of disease. Our data show that M. leprae and its fractions are able to differentially modulate the activity and functionality of IDO‐1 in mDCs by a pathway that involves TLR2, suggesting that this enzyme may play an important role in leprosy immunopathogenesis. Graphical Abstract: Mycobacterium leprae and its fractions are able to differentially modulate the activity and functionality of Indoleamine 2, 3 dioxygenase in human monocyte‐derived dendritic cells via a pathway that involves TLR2.